The perceived legitimacy of managerial influence: A twenty-five year comparison - Ashforth, Blake E. (Journal of business ethics, 1989)
The study examines perceptions of managers, nonmanagerial employees, students, and union officers regarding the legitimacy of managerial influence over various subordinate behaviors and beliefs. The results indicate that: (1) perceived legitimacy has decreased since a comparable study by Schein and Ott in 1962, (2) perceived legitimacy is generally related to proximity to the managerial role, (3) there is a high degree of consensus on the relative legitimacy of influencing various behaviors and beliefs, and (4) only issues of direct relevance to work and task performance are currently perceived as legitimate areas for managerial influence. Theoretical, research, and managerial implications are discussed.